A flexible format LAMP assay for rapid detection of Ebola virus. - Laura C Bonney; Robert J Watson; Gillian S Slack; Andrew Bosworth; Nadina I Vasileva Wand; Roger Hewson (Public Library of Science (PLoS), 2020)
Background The unprecedented 2013/16 outbreak of Zaire ebolavirus (Ebola virus) in West Africa has highighted the need for rapid, high-throughput and POC diagnostic assays to enable timely detection and appropriate triaging of Ebola Virus Disease (EVD) patients. Ebola virus is highly infectious and prompt diagnosis and triage is crucial in preventing further spread within community and healthcare settings. Moreover, due to the ecology of Ebola virus it is important that newly developed diagnostic assays are suitable for use in both the healthcare environment and low resource rural locations. Methodology/principle findings A LAMP assay was successfully developed with three detection formats; a real-time intercalating dye-based assay, a real-time probe-based assay to enable multiplexing and an end-point colourimetric assay to simplify interpretation for the field. All assay formats were sensitive and specific, detecting a range of Ebola virus strains isolated in 1976-2014; with Probit analysis predicting limits of detection of 243, 290 and 75 copies/reaction respectively and no cross-detection of related strains or other viral haemorrhagic fevers (VHF's). The assays are rapid, (as fast as 5-7.25 mins for real-time formats) and robust, detecting Ebola virus RNA in presence of minimally diluted bodily fluids. Moreover, when tested on patient samples from the 2013/16 outbreak, there were no false positives and 93-96% of all new case positives were detected, with only a failure to detect very low copy number samples. Conclusion/significance These are a set of robust and adaptable diagnostic solutions, which are fast, easy-to-perform-and-interpret and are suitable for use on a range of platforms including portable low-power devices. They can be readily transferred to field-laboratory settings, with no specific equipment needs and are therefore ideally placed for use in locations with limited resources.